2021
DOI: 10.3390/toxics9020039
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Mercury, Methylmercury and Selenium in Fish: Insights into Children Food Safety

Abstract: Total mercury (THg), methylmercury (MeHg), and selenium (Se) concentrations were measured in various commercially important fish species. The benefit–risk binomial associated with these chemicals was assessed in children through the probability of exceeding the provisional tolerable weekly intakes (PTWIs) of the contaminants and the Se recommended dietary allowance (RDA). The Se:Hg molar ratios, selenium health benefit values (HBVSe), and monthly consumption rate limits (CRmm) for each species were also calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…Selenium mean concentration in the study ranged from 2.06 to 8.13 mg/kg. The concentration of Se in this study is in line with the finding of [51] who reported values of 0.15 µg g −1 to 0.58 μg g −1 from the Mediterranean area. However, the concentration of Se in this study is higher than the findings of [52] who reported concentration of 0.27 mg/kg to 0.56 mg/kg in Gadus morhus and Sebastes spp respectively.…”
Section: Levels Of Toxic Metals In Fishsupporting
confidence: 92%
“…Selenium mean concentration in the study ranged from 2.06 to 8.13 mg/kg. The concentration of Se in this study is in line with the finding of [51] who reported values of 0.15 µg g −1 to 0.58 μg g −1 from the Mediterranean area. However, the concentration of Se in this study is higher than the findings of [52] who reported concentration of 0.27 mg/kg to 0.56 mg/kg in Gadus morhus and Sebastes spp respectively.…”
Section: Levels Of Toxic Metals In Fishsupporting
confidence: 92%
“…With respect to skates, Barone et al [ 15 ] in a recent paper measured concentrations from 0.58 to 0.67 μg g −1 w.w. in different species from the Mediterranean Sea. Nicolaus et al [ 60 ] find levels between 0.02 and 1.8 μg g −1 w.w. with an average of 0.43 μg g −1 w.w. in Leucoraja circularis from Celtic Sea.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning batoids, the published data are scarce or even non-existent, as in the case of torpedinids. The few studies on skates seem to indicate that consumption of these species provide far more Se than Hg to the consumer [ 15 , 57 , 68 ]. This suggestion is in an agreement with the findings of the current study, which shows a healthy profile of these species and provides a clear example of integration between Se-specific nutritional benefits and the potential Hg-exposure risks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations